Comparative Analysis of Deoxynivalenol Biosynthesis Related Gene Expression among Different Chemotypes of Fusarium graminearum in Spring Wheat - Amarasinghe, Chami C.; Fernando, W. G. Dilantha (Frontiers in Microbiology, 2016)
Fusarium mycotoxins, deoxynivalenol (DON) and nivalenol (NIV) act as virulence factors and are essential for symptom development after initial infection in wheat. To date, 16 genes have been identified in the deoxynivalenol biosynthesis pathway. However, a comparative gene expression analysis in different chemotypes of F. graminearum in response to fusarium head blight (FHB) infection remains to be explored. Therefore, in this study, nine genes that involved in trichothecene biosynthesis were analysed among 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON) and nivalenol (NIV) producing F. graminearum strains in a time course study. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) revealed that the expression of all examined TRI gene transcripts initiated at two days post-inoculation (dpi), peaked at three to four dpi and gradually decreased at seven dpi. The early induction of TRI genes indicates that presence of high levels of TRI gene transcripts at early stages, is important to initiate the biosynthetic pathway of DON and NIV. Comparison of gene expression among the three chemotypes showed that relative expression of TRI genes was higher in 3-ADON producing strains compared with 15-ADON and NIV strains. Comparatively higher levels of gene expression may contribute to the higher levels of DON produced by 3-ADON strains in infected grains.